Adubação nitrogenada da cultura do feijão (Phaseolus vulgaris L), na Zona da Mata de Minas Gerais - Araya V, Rodolfo; Vieira , Clibas; Teixeira Monteiro , A A; Américo Cardoso, Antônio; Brune, Walter (Revista Ceres, 2025)
Three studies on nitrogen fertilization of beans (Phaseolus vulgaris L.) were carried out in the Zona da Mata area, state of Minas Gerais, Brazil.